Participatory Research for Health and Social Well-Being - Abma, Tineke; Banks, Sarah; Cook, Tina.; Dias, Sónia; Madsen, Wendy; Springett, Jane.; Wright, Michael T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This textbook is a comprehensive guide for students interested in using participatory research to improve people's health and well-being. It is especially designed for those working in the fields of health and social welfare who are embarking on participatory research for the first time. It covers all phases in participatory research from "getting started," to "acting for change," "continuing the journey" and "articulating impact." Its unique format helps readers understand the essence of participatory research as a comprehensive approach for doing research which is underpinned by a set of fundamental values. The many real life examples of participatory research projects from around the world inspire readers to find creative ways to manage their own research while opening up new horizons in their work.
Chapter 1. Making the Case: The Arguments for Participatory Research -- Chapter 2. Framing: The Search for a Lens of Understanding -- Chapter 3. Getting Started: The Initiation of a Partnership -- Chapter 4. Shaping: The Co-creation of a Research Design -- Chapter 5. Organizing: Making Plans Together -- Chapter 6. Acting for Change: The Generation of Transformative Action -- Chapter 7. Engaging: The Choice and Use of Participatory Methods -- Chapter 8. Sense Making: The Process of Data Analysis and Interpretation -- Chapter 9. Telling and Showing: The Shared Decisions About Dissemination -- Chapter 10. Capturing and Reflecting for Change: The Generation of Impact -- Chapter 11. Continuing the Journey: The Quest for Sustainable Partnerships -- Chapter 12. Epilogue: Bringing the Threads Together.
Keywords: Sociology -- Methodology; Quality of life; Nursing; Sociological Methods; Quality of Life Research; Nursing